Characterization of KPC-encoding plasmids from two endemic settings, Greece and Italy - Papagiannitsis, Costas C; Di Pilato, Vincenzo; Giani, Tommaso; Giakkoupi, Panagiota; Riccobono, Eleonora; Landini, Giulia; Miriagou, Vivi; Vatopoulos, Alkiviadis C; Rossolini, Gian Maria (The Journal of antimicrobial chemotherapy, 2016)
OBJECTIVES: Global dissemination of KPC-type carbapenemases is mainly associated with the spread of high-risk clones of Klebsiella pneumoniae and of KPC-encoding plasmids. In this study, we explored the population structure of KPC-encoding plasmids from the recent epidemics of KPC-producing K. pneumoniae (KPC-Kp) in Greece and Italy, the two major European endemic settings. METHODS: Thirty-four non-replicate clinical strains of KPC-Kp representative of the early phases (2008-11) of the Greek (n = 22) and Italian (n = 12) epidemics were studied. Isolates were typed by MLST, and blaKPC-carrying plasmids were characterized by S1 profiling, PCR-based replicon typing and RFLP. Transfer experiments by conjugation or transformation were carried out with Escherichia coli recipients. Eleven plasmids, representative of all different restriction profiles, were completely sequenced. RESULTS: The representative Greek strains belonged to 14 sequence types (STs), with a predominance of ST258. The representative Italian strains belonged to three STs, with a predominance of clonal complex 258 (ST258, ST512). The 34 strains carried plasmids of variable size (78-166 kb), either with blaKPC-2 or blaKPC-3 gene embedded in a Tn4401a transposon. Plasmids from Greek strains were mostly of a single RFLP type (A) and resembled the archetypal pKpQIL KPC-encoding plasmid, while plasmids from Italian strains belonged to a more heterogeneous population, showing five RFLP profiles (A, C-F). Types A and C resembled pKpQIL or deletion derivatives thereof, while types D-F included plasmids with hybrid structures between pKpQIL, pKPN3 and pKPN101-IT. CONCLUSIONS: pKpQIL-like plasmids played a major role in the dissemination of blaKPC in Greece and Italy, but evolved with different dynamics in these endemic settings.
Keywords: Epidemics; polymorfismus délky restrikčních fragmentů; Endemic Diseases; karbapenemy; lidé; Plasmids; Itálie; Řecko; bakteriální léková rezistence; Greece; Klebsiella pneumoniae; beta-laktamasy; Electrophoresis, Gel, Pulsed-Field; beta-Lactamases; Humans; multilokusová sekvenční typizace; plazmidy; Bacterial Proteins; Microbial Sensitivity Tests; Escherichia coli; endemické nemoci; mikrobiální testy citlivosti; Klebsiella Infections; Carbapenems; Drug Resistance, Bacterial; Polymorphism, Restriction Fragment Length; Sequence Analysis, DNA; sekvenční analýza DNA; bakteriální proteiny; pulzní gelová elektroforéza; epidemie; infekce bakteriemi rodu Klebsiella; Multilocus Sequence Typing; Italy